Coping with Population Ageing in Hungary - Burns, Andrew (OECD Economics Department Working Papers, 2002)
This paper examines economic challenges posed by the combination of an ageing and declining population in Hungary and develops policy-oriented recommendations for addressing them. The authors identify the scale and specific properties of the demographic problem in Hungary where the population started to decline earlier than in any other OECD country. Public support for the elderly is provided by the social-security pension system and the healthcare system. While the former was reformed with partial success in the late 1990s, the latter developed less successfully, threatening to generate massive deficits in the long run. Projections indicate that even the public pension system may become unsustainable, unless the authorities restore the parameters of the original reform and encourage successfully higher labour force participation. In this context, measures to improve employability of the numerically strong and growing Roma minority are particularly pertinent. The healthcare sector ...